Universality and Contextuality of Islamic Law: a Perspective from Wael B. Hallaq and Thaha Jabir Alwani - Luth, Thohir; Ahmad, Md Yazid (Peradaban Journal of Law and Society, 2023)
The article delves into the concepts of universality and contextuality within Islamic law from the perspectives of two eminent scholars, Wael Bahjat Hallaq and Thaha Jabir Alwani. The research aims to comprehend these scholars' views on the universality and contextuality of Islamic law in the contemporary context. The research methodology involves a meticulous analysis of Hallaq and Alwani's written works and a comprehensive review of pertinent literature. The findings suggest that, while both scholars concur that Islamic law embodies universal values applicable across time, they also underscore the significance of comprehending the social and cultural context when applying Islamic law. Hallaq emphasizes the necessity of a profound understanding of the principles of Islamic law to address contemporary challenges, whereas Alwani highlights the flexibility of Islamic law in adapting to changing times. These findings offer valuable insights into the effective implementation of Islamic law in diverse global and local contexts.